Indian English - Sailaja, P. (Pingali), 1962- (Dialects of English., 2009)
This book is a descriptive account of English as it is used in India. Indian English is a second language to most of its speakers. In its 400-year history it has acquired its own character, yet still looks to native varieties of English for norms. The complex nature of Indian English, which is not really a monolithic entity, is discussed in this book. The book also makes a distinction between what are considered to be standard and non-standard varieties, and provides an overview of the salient features. Indian English includes: *A discussion of the sociolinguistic and cultural factors *The his.